2021
DOI: 10.1089/jayao.2020.0184
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Evidence for Key Positive Psychological Constructs in Pediatric and Adolescent/Young Adult Patients with Cancer: A Scoping Review

Abstract: Introduction: Children and adolescents/young adults (AYAs) with cancer are a vulnerable population susceptible to numerous late effects, such as fatigue and depression, which may diminish their long-term psychological, physical, spiritual, and emotional health. A well-rounded understanding of how positive psychological constructs affect the quality of care and treatment outcomes is therefore warranted. Methods: We conducted a scoping review of 15 positive psychological constructs in children and AYAs with canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 181 publications
(250 reference statements)
1
14
0
Order By: Relevance
“…Nevertheless, children with cancer have rarely been involved in the development of PROMs [ 22 , 23 ]. Consequently, there is only scarce evidence for the content validity of most available PROMs [ 23 , 65 ]. Thus, it is questionable whether they cover children’s priorities.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, children with cancer have rarely been involved in the development of PROMs [ 22 , 23 ]. Consequently, there is only scarce evidence for the content validity of most available PROMs [ 23 , 65 ]. Thus, it is questionable whether they cover children’s priorities.…”
Section: Discussionmentioning
confidence: 99%
“…11 However, there is limited understanding of the salient positive psychological constructs linked to AYALHIV's improved well-being and healthrelated quality of life. Wayant et al (2021), in their scoping review, mapped 15 positive psychological constructs associated with increased quality of life and survival in AYAL with cancer. 12 Well-being, personal growth, hope, meaning in life, self-esteem, vitality and optimism were the most cited positive constructs; 12 these constructs are potentially transferable to AYALHIV.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Conversely, etiological differences between cancer and HIV could also lead to differences in lived experiences, resulting in differential perceptions in positive psychological constructs. 12 For instance, HIV-related stigma (often associated with issues related to HIV’s potential infectiousness) may have a greater impact on mental health functioning in AYALHIV 13 14 when compared with the effects of cancer-related stigma. 15 It is thus critical to contextualise the impacts of positive psychological outcomes in AYALHIV.…”
Section: Introductionmentioning
confidence: 99%
“…Including studies where a minority of patients are older than 39 years has increased the included study yield in a prior article because of the recent recognition of AYAs as patients ages 15-39. 16 Despite placing no language restriction on the database search, we only included studies written in English and Spanish, but document studies in other languages to alert readers of their existence. K.B.…”
Section: Inclusion Criteria and Study Screeningmentioning
confidence: 99%
“…Our scoping review found little standardization in the PROMs used to measure positive psychological constructs and conflicting data about what increases expression of those constructs. 16 Our main recommendations in that scoping review were to work toward the creation of a core set of PROMs that can be used to measure positive psychological constructs. Core outcome sets are an ideal method to standardize the medical literature and promote evidence-based comparison of psychological interventions.…”
mentioning
confidence: 99%